Financial Information In The Context Of Financial Distress Antecedents With The Independent Board Of Commissioners As Moderator - Pristiana, Ulfi; Dutahatmaja, Angga (Universitas Dharma Wacana, 2023)
The primary objective of this study was to examine the impact of funding decisions, investment choices, managerial ownership, and institutional ownership on financial distress. Additionally, we aimed to assess the moderating role of an independent board of commissioners about these independent variables and their effects on financial distress. This research employed a quantitative approach and utilized WarpPLS for analysis. Data collection was carried out through purposive sampling, focusing on a population of 53 companies listed on the IDX, with a sample size of 46 companies. The findings of the research indicated that investment decisions had a significant positive influence on financial distress, whereas funding decisions had no significant impact. Managerial ownership also showed no significant effect, while institutional ownership had a notable negative impact on financial distress. Notably, the independent board of commissioners did not moderate the effect of investment decisions on financial distress but did moderate the impact of funding decisions, managerial ownership (fully), and institutional ownership (partially) on financial distress. The implications of this study are valuable for improving financial management practices in manufacturing companies.